Effects of hexane on protein profile and techno-functional properties of pea protein isolates. (16th April 2023) - Gravel, Alexia; Dubois-Laurin, Florence; Doyen, Alain
Highlights: Pea protein isolates (PPI) were produced by ultrafiltration/diafiltration. Hexane-defatting had no impact on PPI protein profile. Emulsifying and gelation properties of PPI were not impacted by defatting. Hexane-defatting only improved foaming stability of PPI. Abstract: The defatting of legume flours with hexane is usually the first step in producing protein-rich ingredients. However, its impact on protein profiles, zeta potential, surface hydrophobicity and techno-functionality of pea proteins has not been evaluated. Consequently, this work aimed to evaluate the impact of the hexane defatting step on pea protein profiles, surface hydrophobicity and zeta potential, as well as techno-functional properties of non-defatted and defatted pea protein isolates. The results showed that alkaline extraction of hexane-defatted pea flour increased the net surface charge (zeta-potential) and reduced particle size of the pea protein isolate. Moreover, only the foaming properties of pea protein isolate generated from defatted pea flour were improved. Consequently, except for improving foaming properties, the defatting step is not essential for the production of pea protein isolate.